2022
DOI: 10.3389/falgy.2022.915014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in food-related costs during the COVID-19 pandemic among families managing food allergy

Abstract: BackgroundThe COVID-19 pandemic has affected the supply, cost, and demand for certain foods, but it is not clear how these changes have affected food-allergic households.ObjectiveTo describe the changes in food-related costs that have followed COVID-19, as reported by higher- and lower-income households with a food-allergic member.MethodsBetween May 1-June 30, 2020, Canadian households, with at least one food-allergic member, completed an online survey on food shopping and preparation habits before and during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…For families also managing food allergy, concerns regarding food insecurity are even greater, owing to the excess costs of food allergy, which both pre-dated [ 2 ] and has persisted during the pandemic [ 7 ]. Prior to the pandemic, these families spent, on average, $200 more per month on groceries, in comparison to families without food allergy [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For families also managing food allergy, concerns regarding food insecurity are even greater, owing to the excess costs of food allergy, which both pre-dated [ 2 ] and has persisted during the pandemic [ 7 ]. Prior to the pandemic, these families spent, on average, $200 more per month on groceries, in comparison to families without food allergy [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the pandemic, these families spent, on average, $200 more per month on groceries, in comparison to families without food allergy [ 2 ]. These estimates were even higher one two months into the pandemic with high income families indicating that their spending on food had increased $200 per month in comparison to before the pandemic; whereas, lower income families spent additional $100 a month, on average [ 7 ]. The impact of these excess costs is seen in Waves 2 and 3, with an emergence of marginal food insecurity, and in Wave 3, with the near-disappearance of those reporting moderate food insecurity, and an increase amongst those reporting severe food insecurity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Household income also appears to affect how families with food allergy have adapted to changes in the availability, cost, and consumption of food brought about by the COVID-19 pandemic. Research by Golding et al found both higher and lower income households with food allergy reported spending more on groceries in the early months of the pandemic, but higher income households reported an increase that was over twice as large as the lower income families (higher income households: þ$204.69 /month; lower income households: þ$73.24 /month) [23]. It is likely that the larger increase in grocery costs found among the higher income group reflects the fact that higher income households possess greater discretionary income.…”
Section: Influences On Individual and Household-level Costsmentioning
confidence: 99%
“…In addition to severity, evidence can also be cited linking income to spending on food allergy [3 ▪ ,16 ▪ ,23]. In their investigation of the household costs of food allergy in Canada, Golding et al [16 ▪ ] found that higher income families with a child with food allergy reported greater spending on food relative to controls, but the same was not true for lower income families.…”
Section: Influences On Individual and Household-level Costsmentioning
confidence: 99%